Second foreign languages and employability in the Catalonia of the SXXI - Lopez Garcia, Patricia (2019)
Introduction: Despite considering the English language, Lingua Franca par excellence, Catalan companies, due to their growing economic internationalization, demand more and more professionals with skills in foreign languages associated with skills and attitudes linked to employability. These characteristics reflect the needs of the labour market, which implies a strong synergy between universities and companies in order to provide future graduates with the most suitable skills for a quality labour market insertion. Methods: Our analysis is based on the study of two different profiles of graduates, on the one hand, students of the Faculty of Translation and Interpretation of the Autonomous University of Barcelona and on the other hand, students of the Degree in Tourism of Euroaula-University of Girona, two areas in which knowledge of second languages is unavoidable for their subsequent incorporation into the labour market. We will focus on second foreign languages (French, German, Italian, etc.) which are part of the growing needs of the Catalan business sector. Conclusions: The graduates who can accredit linguistic knowledge in two foreign languages, associated with transversal skills linked to employability, are future professionals highly coveted by the world of work. From this perspective, the world of education must try to reconsider the teaching of foreign languages that is more in line with the needs of knowledge, know-how and know how to be.